Women’s Language Features In The Lady Bird Movie - Ni Putu Tifani Puspa Lestari; Ni Luh Sutjiati Beratha; Ni Wayan Sukarini (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2024)
This research analyzed women’s language used in Lady Bird movie, focusing on Christine’s utterances as the main character of the movie. The data was collected using documentation method and note-taking technique. The descriptive qualitative method was used to analyze the data based on Lakoff’s theory on women’s language features and Pearson’s theory on language functions. The results were presented in sentences. The result showed that Christine uses lexical hedges or fillers, tag questions, rising intonation on declaratives, empty adjectives, intensifiers, hypercorrect grammar, super polite forms, avoidance of strong swear words, and emphatic stress. Precise color term is found in Marion’s utterance. These features are used for expressing uncertainty, seeking responses, softening utterances, initiating discussion, and conveying emotion, according to Pearson’s five language functions.